47th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2009
DOI: 10.2514/6.2009-1399
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Of Radiation, Ablation, And Free Energy Minimization Modules For Coupled Simulations of Hypersonic Flow

Abstract: A description of models and boundary conditions required for coupling radiation and ablation physics to a hypersonic flow simulation is provided. Chemical equilibrium routines for varying elemental mass fraction are required in the flow solver to integrate with the equilibrium chemistry assumption employed in the ablation models. The capability also enables an equilibrium catalytic wall boundary condition in the non-ablating case. The paper focuses on numerical implementation issues using FIRE II, Mars return,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Recent work 32 has extended this capability to accommodate the injection of a gas containing the elements C, H, O, and N. The wall is assumed to be in chemical equilibrium at a specified wall temperature. The elemental composition at the wall is obtained by solving the elemental continuity equations 45 , which account for diffusion, convection, and mass injection of the char and pyrolysis gas.…”
Section: Flowfield Modeling With Ablation Products and Radiationmentioning
confidence: 99%
“…Recent work 32 has extended this capability to accommodate the injection of a gas containing the elements C, H, O, and N. The wall is assumed to be in chemical equilibrium at a specified wall temperature. The elemental composition at the wall is obtained by solving the elemental continuity equations 45 , which account for diffusion, convection, and mass injection of the char and pyrolysis gas.…”
Section: Flowfield Modeling With Ablation Products and Radiationmentioning
confidence: 99%
“…The strong thermochemical equilibrium conditions cause sharp gradients in the temperatures and number densities at the shock (as a result of the abrupt change from the free-stream quantities to the post-shock quantities), which were found to cause stability problems in the flowfield solution procedure. To accommodate this, the recently developed 32 general chemical equilibrium option in LAURA was applied. This option treats a single temperature and solves the elemental continuity equations.…”
Section: Mars-return Benchmark Casementioning
confidence: 99%
“…Applying state-of-the-art flowfield (LAURA) and radiation (HARA) models, the present work examines the influence of ablation on the radiative heating for lunar and Mars return conditions. A T brief discussion of this recently developed capability 32 , which consists of a 22-species thermochemical nonequilibrium LAURA flowfield model with coupled HARA radiation and an ablating wall, is discussed in Section II. In Section III, the extension of HARA to treat carbon and hydrogen species is discussed and the sources of the required data are listed.…”
Section: Introductionmentioning
confidence: 99%
“…Program LAURA 11,15 simulates the coupled radiation and ablation in the shock layer over a vehicle entering a planetary atmosphere at hypersonic velocities. This code was chosen as a starting point for simulation of the production rig because the algorithms for dealing with high temperature, reacting gas mixtures and tightly coupled ablation and radiation for carbon based ablators are already well established.…”
Section: Methodsmentioning
confidence: 99%
“…10 In the case of flow in chemical equilibrium the elemental continuity equations are solved and a free energy minimization is implemented in every control volume to solve for species mass fractions as a function of elemental mass fraction, temperature, and pressure. 11 Early equilibrium simulations had been run with only a four species model that neglected B 2 . These simulations indicated that the presence of B 2 significantly diminished the amount of BN in the upper part of the plume.…”
Section: B Gas Propertiesmentioning
confidence: 99%